HUBUNGAN MOTIVASI DAN MASA KERJA DENGAN TINGKAT KEPATUHAN PERAWAT DALAM MENGGUNAKAN ALAT PELINDUNG DIRI (APD) DI RUANG RAWAT INAP RUMAH SAKIT ROYAL PRIMA JAMBI - Gusrani; Dini Suryani (Nightingale: Journal of Nursing, 2024)
Hospitals are not only places of treatment but can be a source of infection. Infections that are acquired from hospitals are usually acquired by patients during the treatment process at health facilities which are called nosocomial infections (HAIs). HAIs are still a health problem faced by developing countries, including Indonesia. Efforts that can be made to prevent HAIs are nurses' compliance with using PPE. This study aims to determine the relationship between length of service and motivation in using PPE in the inpatient ward at Royal Prima Hospital Jambi in 2023. This research is a quantitative study with a cross-sectional approach. The research was carried out on 1 September 2023 – 10 September 2023 at the Royal Prima Jambi Hospital. The results analyzed using the chi-square test. The results show that there is no relationship between the length of service and nurses' compliance with using PPE in the inpatient room at Royal Prima Jambi Hospital in 2023 with a p-value of 0.614. On the other hand, research shows that there is a relationship between motivation and nurses' compliance with using PPE in the inpatient room at Royal Prima Jambi Hospital in 2023 with a p-value of 0.03. Conclusion Motivation is a factor that influences nurses' compliance with using PPE. So, to increase nurse compliance, hospitals are expected to hold outreach, and training and provide rewards to nurses who are compliant in using PPE.